2010
DOI: 10.4314/ajbr.v11i1.50673
|View full text |Cite
|
Sign up to set email alerts
|

Clinical signs and organ pathology in rats exposed to graded doses of pyrethroids- containing mosquito coil smoke and aerosolized insecticidal sprays

Abstract: Morphological changes in tissues/organs of weanling Albino rats exposed to graded doses of popular brands of pyrethroids-containing insecticidesmosquito coil and aerosolized spray were studied over a period of 18 days. Rats were exposed to 0.4, 0.8, 1.2 and 1.6mg/kg BW of active ingredients in aerosolized insecticidal spray for 15, 30, 45 and 60 seconds, in two divided doses daily for 18 days. Control rats were not exposed. Early clinical signs include irritability, head shaking and scratching of nostrils; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
10
14
0
Order By: Relevance
“…Histopathological evaluation of mosquito coil effect had shown the impact on the kidney, 16 weeks post exposure, which demonstrates full congestion around the glomerular tuft, the study agrees with Taiwo et al 2008 which demonstrated glomerula and tubular degeneration, necrosis, thrombosis and vasculitis to mosquito coil and varying insecticidal spray fumes in experimental rats. The study is also in line with earlier published work of Garba et al 2007a which demonstrated serve multifocal congestion, cystic dilation in the medulla of kidney tissue exposed to pyrethroid based mosquito coil.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Histopathological evaluation of mosquito coil effect had shown the impact on the kidney, 16 weeks post exposure, which demonstrates full congestion around the glomerular tuft, the study agrees with Taiwo et al 2008 which demonstrated glomerula and tubular degeneration, necrosis, thrombosis and vasculitis to mosquito coil and varying insecticidal spray fumes in experimental rats. The study is also in line with earlier published work of Garba et al 2007a which demonstrated serve multifocal congestion, cystic dilation in the medulla of kidney tissue exposed to pyrethroid based mosquito coil.…”
Section: Discussionsupporting
confidence: 85%
“…The elevated activities of AST, ALT ALP enzymes observed in rats exposed to both transfluthrin and d-allethrin insecticides suggest hepatic damage or dysfunction; high concentrations of these enzymes in hepatic tissues of dogs, cats and primates have been linked to hepatocellular damage (Kaneko & Cornelius 1980, Hall et al 2001). This was confirmed by histopathological examination of rats exposed to transfluthrin and d-allethrin mosquito coil smoke for eight, 12 and 16 weeks in this study, which indicates generalized intracellular accumulations and severe sinusoidal congestion, which also have been demonstrated (Garba et al 2007b, Taiwo et al 2008, Aslam et al 2010). This study therefore demonstrates potential damage to the liver arising from the use of transfluthrin and d-allethrin mosquito coil.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Literature report illustrated that free radical‐mediated oxidative stress was responsible for the toxicity of pesticides (Abdollahi et al, ). CYP can induce degenerative changes in various organs including the lung, liver, brain, kidney, and heart (Taiwo et al, ). In the present experiment, α‐CYP induced a significant increase in the level of MDA in lung tissues.…”
Section: Discussionmentioning
confidence: 99%